PENGARUH KEBUDAYAAN ISLAM DI MINAHASA MASA KOLONIAL: BERDASARKAN TINGGALAN ARKEOLOGI - Irfanuddin Wahid Marzuki (Balai Arkeologi Bali, 2020)
This article discusses about the influence of Islamic culture in the land of Minahasa of North Sulawesi Province based on archaeological studies. Minahasa is the biggest ethnic area in North Sulawesi Province, with the majority of the population being Christians. Islam arrival in Minahasa carried by Arab traders, fisherman from North Maluku, Bugis, Makasar, Gorontalo and political prisoners from Java and Sumatera. The early history of Islam in Minahasa, acculturation process, development, and Islamic influence in Minahasa can be traced by using archaelogical studies based on existing physical cultural. Research on Islamic culture in Minahasa specifically based on archaeological studies has not been done before. The previous researches of the same topic were mostly conducted through nonphysical culture. The result of the observation reveals that the influence of Islamic culture in Minahasa comprises of some Islamic Settlements, Mosques, and Islamic Cemetery. The influence of Islamic culture in Minahasa coastal area and inland has different characters due to different historical background, socio cultural, and political background of the Islamic communities. Artikel ini membahas mengenai pengaruh kebudayaan Islam di tanah Minahasa, Propinsi Sulawesi Utara berdasarkan tinggalan arkeologi. Minahasa merupakan wilayah etnis terbesar di Propinsi Sulawesi Utara dengan mayoritas penduduk beragama Kristen. Agama Islam di Minahasa dibawa oleh pedagang-pedagang Arab serta, nelayan dari Maluku Utara, Bugis, Makasar, Gorontalo dan tahanan politik dari Jawa dan Sumatera. Dengan menggunakan kajian arkeologi, dapat ditelusuri sejarah awal masuknya Islam, proses akulturasi yang terjadi, perkembangan dan pengaruh Islam di Minahasa berdasarkan tinggalan kebudayaan fisiknya. Penelitian mengenai kebudayaan Islam di Minahasa dengan menggunakan kajian arkeologi secara khusus belum pernah dilakukan, penelitian-penelitian sebelumnya mengkaji dengan menggunakan tinggalan kebudayaan non fisik yang ada. Hasil pengamatan di lapangan, pengaruh kebudayaan Islam yang terdapat di Minahasa berupa: permukiman Islam, masjid, dan pemakaman (kubur) Islam. Terdapat adanya perbedaan pengaruh kebudayaan Islam di wilayah pesisir dengan pedalaman Minahasa yang disebabkan perbedaan latar belakang sejarah, sosial budaya, dan politik masyarakat Islam pesisir dan pedalaman Minahasa.